Protein S-100B: a prognostic marker for cerebral damage - Stroick, Mark Gregor; Fatar, Marc; Ragoschke-Schumm, Andreas; Faßbender, Klaus; Bertsch, Thomas; Hennerici, Michael G. (Current medicinal chemistry, 2006)
The assessment of S-100B in acute neurological disorders such as global hypoxia, ischaemic or haemorrhagic stroke and traumatic brain injury reflects severity of symptoms and outcome. However, the temporal profile of S-100B release depends on topography, intensity and pathophysiology of the damage e.g. immediate release after traumatic brain injury following the acute destruction of neuronal tissue or delayed release after ischaemic stroke in which gradual breakdown of the blood-brain barrier plays a crucial role. In chronic brain diseases, knowledge about the clinical value of quantification of S-100B is scarce and further evaluations are needed. This review considers both conditions for S-100B measurement and illustrates advantages and limitations in comparison with clinical and neuroimaging data.